2018
DOI: 10.1016/j.neuron.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Related Plasticity in Dendrite-Targeting Layer 1 Interneurons

Abstract: SummaryA wealth of data has elucidated the mechanisms by which sensory inputs are encoded in the neocortex, but how these processes are regulated by the behavioral relevance of sensory information is less understood. Here, we focus on neocortical layer 1 (L1), a key location for processing of such top-down information. Using Neuron-Derived Neurotrophic Factor (NDNF) as a selective marker of L1 interneurons (INs) and in vivo 2-photon calcium imaging, electrophysiology, viral tracing, optogenetics, and associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
257
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(313 citation statements)
references
References 74 publications
33
257
3
Order By: Relevance
“…225mice, we measured the change in pupil diameter in response to the auditory cues (CSversus CS + ) during habituation and recall(Abs et al 2018;Garcia-Junco-Clemente et al 2019, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…225mice, we measured the change in pupil diameter in response to the auditory cues (CSversus CS + ) during habituation and recall(Abs et al 2018;Garcia-Junco-Clemente et al 2019, …”
mentioning
confidence: 99%
“…Notably, under freely behaving conditions, the mice showed a prominent and discriminative fear response to the CS+ ( Figure 3B, CSfreezing: 20.86% ± 2.97%, CS + freezing: 71.75 ± 5.11%, n = 21 mice; p < 0.001, paired t test), indicating successful fear memory learning. To estimate fear expression in head-fixed mice, we measured the change in pupil diameter in response to the auditory cues (CSversus CS + ) during habituation and recall (Abs et al 2018; Garcia-Junco-Clemente et al 2019, Figure 3C). Following fear conditioning, the pupil evoked responses 230 increased for the CS + but not for the CS -( Figure 3D-F; CSbefore: 0.46% ± 1.46%, CS + before: -0.57% ± 0.62%; n = 7 mice, 263 trials; p = 0.47, paired t test; CSafter: 1.88% ± 0.45%, CS + after: 10.2% ± 2.15%, n = 9 mice, 352 trials; p < 0.01 paired t test).…”
mentioning
confidence: 99%
“…NGFCs receive inputs from many afferent cortical and subcortical areas that project to L1 of the cortex (Abs et al, 2018). In general, these inputs signal top-down information from higher order brain areas that control the processing of bottom-up information that is locally processed in the specific cortical area (Larkum, 2013).…”
Section: Converging Modulatory Pathwaysmentioning
confidence: 99%
“…Interestingly, NGFCs also engage a particularly slow form of ionotropic inhibition that reflects the slow GABA dynamics within the synaptic cleft as well as the slow receptor kinetics of highaffinity GABAAR in the postsynaptic membrane (Tamas et al, 2003;Karayannis et al, 2010;Schulz et al, 2018). A recent study demonstrated that a large fraction of L1 interneurons that express Neuron-Derived Neurotrophic Factor (NDNF) inhibits postsynaptic pyramidal neurons by a combination of slow GABAAR and GABABRmediated IPSCs as it is typical for NGFCs (Abs et al, 2018). Furthermore, NDNF+ interneurons effectively inhibited Ca 2+ spikes evoked in the apical dendrite of L5 pyramidal neurons (Abs et al, 2018).…”
Section: Mechanisms Of Gababr-mediated Modulation Of Dendritic Integrmentioning
confidence: 99%
See 1 more Smart Citation